Revisiting the 3α reaction rates in helium burning stars - T. Depastas; S.T. Sun; H.B. He; H. Zheng; A. Bonasera (Physics Letters B)
Helium burning is one of the most fundamental steps of stellar nucleosynthesis, as it describes the formation of life-determining element of carbon, while it plays a key role in the evolution of Red Giant, accreting White Dwarfs and Neutron Stars. In this work we develop a generalized statistical theory for the 3α reaction, which is based on the use of the Imaginary Time Method, along with the semi-classical Hybrid α-Clustering (HαC) and Neck Model (NM) frameworks. The results compared to the methodology and data of the NACRE collaboration, following in several orders of magnitude discrepancies, especially at low temperatures. This may be crucial for the early dynamics of helium burning stars.